Ammonium transport experiments in soil columns: estimating transport parameters - Trang, Nguyen Thi Minh; Hong, Le Dinh; Tri, Vo Khac (Vietnam Journal of Science and Technology, 2017)
Soluble contaminant transport into groundwater aquifers is one of the current  practical problems occuring not only in Vietnam but also in many countries around the world. In this paper, according to the main objective of estimating the ammonium (NH4+) transport parameters in soil and groundwater aquifer of  Con Son Island - District Con Dao, experiments with conservative tracers (sodium chlorides) and ammonium chlorides solution had been carried out on the Con Son soil columns. The transport parameters are estimated under supportting of software Hydrus 1D using the inverse parameter estimation method. Results of the experiments showed that dispersion coefficient, distribution coefficient and mass transfer coefficient characterized the ammonium transport process in the Con Son soil and aquifers are compatible with mechanical and physical properties of Con Son soil matrix and porous media.